Real Wages and the Demand for Skilled and Unskilled Male Labour in Ghana's Manufacturing Sector: 1991-1995. - Teal, F (Elsevier, 2000)
Real wage rates in Ghana have fallen substantially over the last 20 years. In this paper survey data for the years 1991-95 is used to assess the changes which have occurred in the 1990s. It is shown that the real wage rate for the unskilled has continued to fall. Factor share equations for skilled and unskilled labour are estimated, which show the rise in skilled wages leading to substitution to unskilled labour but no rise in the share of skilled labour in income. The own price elasticities of skilled and unskilled labour are estimated at -0.44 and -0.52, respectively.